2009
DOI: 10.1111/j.1365-2516.2008.01956.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of recombinant activated factor VII vs. activated prothrombin complex concentrate for patients suffering from haemophilia complicated with inhibitors: a Bayesian meta‐regression

Abstract: The optimal on-demand treatment of joint bleeds in haemophilia patients with inhibitors is a source of debate, with studies reporting various efficacy levels for different drugs and dosage regimens. To analyse, in a unified Bayesian meta-regression model, the published efficacy of recombinant activated factor VII (rFVIIa) and/or activated prothrombin complex concentrate (aPCC) as on-demand treatments for joint bleeds in haemophilia patients with inhibitors. A systematic search was carried out to identify studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 59 publications
1
54
0
3
Order By: Relevance
“…Buscando validar os resultados encontrados e minimizar o impacto das limitações acima expostas, foi realizada uma busca por estudos farmacoeconômicos que avaliaram o rFVIIa em diferentes cenários e países. Sete estudos foram avaliados visando demonstrar e comparar os principais aspectos econô-micos do tratamento em outras populações e comprovaram os resultados encontrados neste estudo (Dundar et al, 2005;Ozelo et al, 2007;Putnam et al, 2005;Seremetis et al, 2006;Lyseng & Plosker, 2007;Treur et al, 2009;Knight et al, 2003). De maneira geral, os estudos concluíram que o rFVIIa foi mais eficaz e mais economicamente viável comparado ao CCPa, quando utilizado como tratamento de primeira linha dos episódios hemorrágicos leves a moderados.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Buscando validar os resultados encontrados e minimizar o impacto das limitações acima expostas, foi realizada uma busca por estudos farmacoeconômicos que avaliaram o rFVIIa em diferentes cenários e países. Sete estudos foram avaliados visando demonstrar e comparar os principais aspectos econô-micos do tratamento em outras populações e comprovaram os resultados encontrados neste estudo (Dundar et al, 2005;Ozelo et al, 2007;Putnam et al, 2005;Seremetis et al, 2006;Lyseng & Plosker, 2007;Treur et al, 2009;Knight et al, 2003). De maneira geral, os estudos concluíram que o rFVIIa foi mais eficaz e mais economicamente viável comparado ao CCPa, quando utilizado como tratamento de primeira linha dos episódios hemorrágicos leves a moderados.…”
Section: Discussionunclassified
“…Assim, para a estimativa dos custos e desfechos dos tratamentos, foram reproduzidas as estruturas das árvores de decisão de dois modelos internacionais já publicados, que acompanharam pacientes com hemofilia complicada por inibidores no tratamento de episódios de sangramento leve a moderado. Esses modelos foram extraídos de uma busca na literatura por estudos econômicos (You et al, 2009;Dundar et al, 2005;Ozelo et al, 2007;Putnam et al, 2005;Seremetis et al, 2006;Lyseng & Plosker, 2007;Treur et al, 2009;Knight et al, 2003;Jiménez-Yuste et al, 2013).…”
Section: Estrutura Do Modelounclassified
See 1 more Smart Citation
“…The evidence base has been systematically reviewed using two approaches by Iorio et al 12 and Treur et al 13 Iorio et al summarised the evidence from the two available head-to-head crossover multicentre randomised controlled trials, 14,15 concluding that rFVIIa and aPCC were found to be similar in efficacy Treur et al 13 provided a comprehensive appraisal of all the available randomised and non-randomised evidence from 17 studies and 382 patients treated with rFVIIa and 317 treated with aPCC, 11,15-24 using a Bayesian approach to predict the likelihood of response 12, 24 and 36 hours after three-hourly 90μg/kg rFVIIa or 75IU/kg aPCC. The results showed rFVIIa to be the dominant strategy with a 66, 88…”
Section: Evidence Of Efficacymentioning
confidence: 99%
“…Currently, two bypassing agents, plasma-derived activated prothrombin complex concentrates (APCC, FEIBA ® ) and recombinant activated factor VII (rFVIIa, NovoSeven ® ), are available for the management of bleeding in hemophilia patients with inhibitors including acquired hemophilia patients. Retrospective studies showed the efficacy of rFVIIa and APCC in 12~36 h in a standard administration regime is assessed to be 66~95% and 39~76%, respectively [3]. A recent comparative study seemed to indicate equivalence between rFVIIa and APCC [4]; however, a considerable number of patients experience treatment failure or insufficient efficacy.…”
Section: Introductionmentioning
confidence: 99%